Preparation and Properties Analysis of Chlorinated Butyl Rubber (CIIR)/Organic Diatomite Damping Composites - Sheng, Zeyuan (Materials (Basel), 2018)
In this work, a novel type of diatomite was prepared with a limited content of hindered phenol groups grafted on its hydrophobic surface. The obtained samples were characterized for their surface groups, particle morphology, pore structure, and thermal behaviors. Then, modified diatomite (MDT) was used in preparation of reinforced chlorinated butyl rubber (CIIR) composites by mechanical blending method. The powder of MDT can be uniformly dispersed in CIIR matrices and the compatibility was good. In addition, the MDT showed a positive effect on damping performance of CIIR composites. A blending ratio of CIIR/MDT = 100/10 presented the best damping performance and the damping temperature range (tan δ > 0.7) was extended from 60 to 70 °C. The variable temperature FTIR spectra showed the presence of hydrogen bonds between the hydroxyl groups and chloride atoms in the CIIR matrices, and a blue shift exhibited when these hydrogen bonds were dissociated. Hence, these CIIR composites provided good damping behaviors and supplied a novel and promising way for preparation of high damping rubber composites with broad temperature ranges.